The Dialectic of Ideas About Urban Restoration in Indonesia; The Political Communication of Presidential Candidates at The Apeksi Forum in Makassar - Ropingi el Ishaq,; Prima Ayu Rizqi Mahanani, (Mediakita, 2025)
The dialectic of ideas of the presidential candidates become important for the people in taking the vote. This research aims to the ideas of the presidential candidates delivered in the forum related to urban restoration. The analysis of the study uses critical discourse analysis with observation and documentation methods. The results of the study that Ganjar Pranowo presented ideas related to the programs he run in the provincial government. He mostly talked about the importance of accountability and transparency as a manifestation of his election promise. He did not discuss the city dynamics. He talked a little on the importance of the local government to be actively utilize the global market. His political background and experiences did not give support to formulate the concept of urban restoration. Anies Rasyid Baswedan systematically explained the problems, challenges, and principles of an ideal city that must be considered and implemented by the local governments. The problems of urbanization, fiscal capacity, social disparities in urban communities, environmental conditions, and the road map that were needed to be carried out by the mayors and their staffs were presented coherently. His bright ideas on city cannot be separated from his insight and experiences. He was once the Rector of Paramadina University. He also got many achievements in serving as the Governor of DKI Jakarta. Meanwhile, Prabowo Subianto did not mention about city problems. Prabowo only emphasized the downstream that becomes the state government’s program will later be financially fruitful for the mayors.